Kemampuan Literasi Digital dalam Pembelajaran Teks Eksplanasi Siswa di SD Negeri 4 Made - Kinanti, Anindyah Lyra Syashi; Octaviani, Emy Masfufah; Putri, Vivi Yusnita; Humairah, Humairah (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
Technological developments require individuals to adapt to developments, especially elementary school students. The very rapid development of technology makes learning activities easier. Digital literacy is learning that is influenced by technological developments, digital literacy can help increase students' knowledge. This research method is a type of qualitative research method, namely all the information in this research is presented in the form of words or sentences. This research uses descriptive analysis, namely a description of facts or material obtained from the field. In the current era, students' reading levels are very low, especially in the current era of technological development, therefore researchers want to know students' literacy levels, especially the digital literacy skills that students have mastered. Elementary school students' digital literacy skills in learning are very good, students have made maximum use of their digital literacy skills, such as searching for information via the internet and checking the correctness of information as well as using the internet to facilitate their learning activities. The conclusion that can be obtained is that digital literacy is an activity that is very necessary, with literacy activities students can obtain new information to increase students knowledge.